Self-Efficacy of Exercise in Older Adults with Diabetes: A Concept Analysis - Somsak Thojampa; Chawapon Sarnkhaowkhom; Sirikanok Khankhajhon; Roongtiva Boonpracom; Amaraporn Puraya; Wuttichai Sahattecho (Universitas Airlangga, 2020)
Introduction: Self-efficacy is defined as a person's own judgment of their capabilities to perform a specific activity to attain a particular outcome. The concept of self-efficacy of exercise in older adults with diabetes may still be unclear, so it is essential to elucidate its meaning for better understanding in this concept. This paper aims to explore the meaning of self-efficacy with regard to exercise in older adults with diabetes. Methods: Using the Walker and Avant concept analysis, it discusses cases showing diabetic Thai people and how they manage their health behavior changes, such as with exercise. Results: Analysis of the concept of self-efficacy in terms of its defining attributes, antecedents, consequences, and empirical referents provides information related to clinical usefulness. It helps healthcare professionals communicate the same notion when discussing self-efficacy and can distinguish this concept from other related concepts. Conclusion: Analysis of the concept of self-efficacy provides information related to exercise in older adults and can assist healthcare professionals in communicating the same notion when discussing the concept.